Estimation of volatile compounds emission rates from the working face of a large anaerobic landfill in China using a wind tunnel system. (June 2015) - Liu, Yanjun; Lu, Wenjing; Li, Dong; Guo, Hanwen; Caicedo, Luis; Wang, Chi; Xu, Sai; Wang, Hongtao
Abstract: Municipal solid waste landfills are one of the major sources of odor complaints. The determination of volatile compounds (VCs) emissions and their rates is a necessary prerequisite to calculate and study VCs dispersion and control. In this study a wind tunnel system has been introduced to investigate the VCs emission rates from the working face of a large anaerobic landfill in China. The VCs in gas samples were characterized by gas-chromatograph–mass-spectrometer. The emission rates of VCs increased linearly with sweeping velocity (0.1 m·s −1 to 0.5 m·s −1 ), and 0.28 m·s −1 was selected as the recommended practical operation sweeping velocity. The VCs emission rates on the working face at the landfill site were investigated during the course of a day. 31 chemical species divided into six chemical groups were quantified with the following emission rates: oxygenated compounds: 205.73–750.00 μg·m −2 ·s −1, hydrocarbons: 61.82–220.37 μg·m −2 ·s −1, aromatics: 15.55–40.11 μg·m −2 ·s −1, halogenated compounds: 11.71–31.57 μg·m −2 ·s −1, terpenes: 2.71–18.70 μg·m −2 ·s −1, and sulfur compounds: 1.29–10.84 μg·m −2 ·s −1 . The highest average emission rates of VCs were found from midnight to dawn (1:00–7:00). These results provide key input parameters to users of VCs dispersion models to calculate buffer distances. Highlights: A wind tunnel system was introduced to measure VCs emission rates in a landfill. The emission rates increased linearly with sweeping velocity (0.1–0.5 m·s −1 ). The highest average emission rates of VCs were found from mid night to dawn. Oxygenated compounds were the most abundant compounds on the working face.